Hip fractures in the Portuguese archaeological record - Curate, Francisco (2011)
Fractures are ubiquitous in the archaeological record but the majority of these are the consequence of a traumatic incident and do not reflect any loss of strength inherent to the bone. So-called fragility fractures, particularly hip fractures, are considered uncommon occurrences in skeletal populations from the past. Nevertheless, evidence of this type of fracture in the archaeological record is increasing. A methodical search for possible hip fractures in the excavation reports, theses and monographs housed in the Department of Anthropology of the University of Coimbra presented an occasion to describe six hip fractures, previously unpublished, from different Portuguese archaeological sites and to challenge the widespread assumption that hip fractures were nearly non-existent in the past.